Un estudiante en la Residencia DYA. Cartas de Emiliano Amann a su familia (1935-1936) / A Student of the Residence DYA. Letters of Emiliano Amann to his family (1935-1936) - José Carlos Martín de la Hoz; Josemaría Revuelta Somalo (Studia et Documenta)
Twenty one letters, wrote between October of 1935 and July of 1936, by the young student Emiliano Amann Puente, to his family, during the time he lived in the Residence DYA, of Madrid were publicated. These letters constitute a historic resource of the first years of the Work of God, because they reflect the life in the first residence, and also the relationship that he established with San Josemaría Escrivá de Balaguer and with other members of the Work. The letters are preceded by an extense introduction, which consists in a brief of its content, and it also gives notice of the situation of the country during those months previous to the beginning of the Civil War.